The Analysis of Figurative Language in Little Mix’s Third Album Entitled “Get Weird” - Ni Kadek Ayu Prawita; I Gusti Ayu, Vina Widnyana Putri; I Wayan, Juniartha (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
This research aims to identify the kinds of figurative languages used in the chosen song lyrics of Little Mix album entitled